The Terracotta Plaques of Pagan: Indian Influence and Burmese Innovations. (13th November 2013) - Rao, Vinay Kumar
Since its inception Buddhist art aimed to make the Buddhist disciples well aware with the life and teachings of Buddha. The Buddhist followers had a belief that the attainment of Buddhahood was not an outcome of a single birth but was a successive effort and practice of ten pāramitās in his previous births. Though the origin of Jātakas was in India but its final and complete compilation was finalised in Sri Lanka by the scholars of Buddhaghoṣa School. The life scenes of Buddha in form of Jātakas depictions are ever preferred theme in Buddhist art and were carved with equal enthusiasm and potential elegance in every period irrespective to any political and social limitations. Buddhism entered Myanmar in three inflows, first in 5th Century CE through north-eastern India, secondly during 7th century CE through religious transformation from Sri Lanka and finally in 10–12 century CE through eastern India. The period between 8th-12th centuries CE in India has been considered as a cradle of encouraging heterodox creeds and sects representing both Hinduism and Buddhism which were found to exist side by side. The art practiced during this period was flourished on well designated artistic paradigms of Gupta period but had a deep influence of Pāla art. The intense trade activities between eastern India and South East Asia and unstable political condition of India encouraged the Indian artist to look for new territories where he can easily perform his art. Pagan in central Myanmar provided suitable political and religious environment to these sculptors. As result the art and architecture performed in terracotta plaques of Pagan and its Buddhist religious monumental architecture attained deep influence of eastern India but the art of central Myanmar was not a mere repetition of its Indian neighbourhood but is evident with many local experiments and innovations. The paper is intended intends to make present a brief analysis of the artistic style, technique of engraving legends on plaques in Pagan with its motivation from Pilak (Tripura, India), Pahārpur and Maiāmatī (Bangladesh)